Analisis Pidana Terhadap Pembakaran Lahan dengan Cara Membakar - Muhammad Shaleh; Fitri Wahyuni; Bambang Sasmita Adi Putra (MAN 4 Kota Pekanbaru, 2026)
Land burning remains a persistent legal issue in Indonesia despite its prohibition under Law Number 32 of 2009 on Environmental Protection and Management. This reflects a gap between legal norms (das sollen) and their enforcement (das sein). This study examines the regulation of land burning under Indonesian criminal law, analyzes the elements of the offense and forms of criminal liability, and identifies normative obstacles to effective law enforcement. Using a normative juridical method with a library research approach, the study analyzes primary legal materials, including Law Number 32 of 2009 and Law Number 1 of 2023 on the Indonesian Criminal Code, supported by relevant secondary sources. The findings show that land burning is regulated through complementary environmental and criminal law provisions. Criminal liability applies to individuals, those giving orders, and corporations, with sanctions determined by intent or negligence. However, enforcement remains limited by difficulties in proving intent, regulatory disharmony, and sanctions that insufficiently emphasize environmental restoration. The study recommends regulatory harmonization and criminal law reform oriented toward sustainable ecological recovery.